Cognitive Profile of Children with Neurofibromatosis and Reading Disabilities - Cutting, Laurie E. (2010)
A large percentage of children with Neurofibromatosis Type 1(NF-1) have learning disabilities, often in the realm of reading. Previous studies have indicated that children with NF-1 show a neuropsychological profile similar to idiopathic reading disabilities (IRD); however, studies typically have not subdivided children with NF-1 into those who do and not have RD (NF+RD and NFnoRD, respectively). The current study examined the cognitive profile of children with NF-1 with and without RD and compared them to children with IRD as well as to typically developing readers (Controls). Findings showed that children with NF+RD performed similarly to children with IRD on phonological, rapid naming, and reading comprehension measures; however, children with NF+RD displayed pronounced visual spatial deficits as compared to IRD and Control groups. In addition, when comparing the NF-1 groups to each other as well as to the CNT and IRD groups, the current study reported that there were no oral language differences; lack of findings in the realm of oral language was attributed to the fact that groups were equated on IQ. Overall, findings suggest that a more refined classification of children with NF-1 may be helpful for tailoring academic interventions.